DUKUNGAN SOSIAL-EMOSIONAL KEPALA SEKOLAH SEBAGAI UPAYA PENCEGAHAN TEACHER BURNOUT PADA GURU SEKOLAH DASAR - Setiaji, Soma; Farih Kurniawan, Wildan; Mariyani, Anna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Teacher burnout has become a significant issue in the field of education. This study aims to explore the factors that potentially contribute to teacher burnout and to examine principals’ social-emotional support as a strategy to prevent teacher burnout at SDN 2 Bogorejo and SDN 3 Bogorejo. A qualitative approach with a case study method was employed in this research. Data were collected through triangulation techniques, including in-depth interviews, participant observation, documentation, and questionnaires. Source triangulation involved research informants consisting of the principals and all teachers in both schools. Data analysis used the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that potential factors contributing to teacher burnout include student characteristics, policy changes, administrative demands, salary, and the distance between home and school. Principals provide social-emotional support to prevent teacher burnout in the form of empathy, interpersonal care, supportive presence, instrumental support, informational support, appreciation, and the creation of a positive work climate. The implementation is carried out through early detection of burnout, followed by the provision of support through principals’ daily leadership practices. Social-emotional support has been shown to function as a protective factor in preventing teacher burnout.